Sustainable agro-forestry in Myanmar: From intentions to behavior - Calkins P. (2014)
Environmental degradation, natural disasters, and urbanization have intensified pressure on Myanmar's once unparalleled forests. This contrastive study of 200 households in two eco-marketing zones in Myanmar (accessible Central Myanmar vs. isolated Rakhine State) uses regression analysis to test three hypotheses derived from the previous literature to explain behavioral intentions and positive/negative environmental behavior. All three hypotheses were rejected, suggesting strong country specificity in selecting optimal behavior-based policies for forest conservation and non-destruction. Policy orientations were formulated to help reverse environmental degradation, promote community-oriented activities toward positive environmental behaviors, and provide sustainable pathways out of poverty for rural households. The main problem in Central Myanmar emerges as one of motivation, which could be promoted by public awareness programs, outside employment and financial viability. In Rakhine State, where the environmental footprint is heavier, policies should empower conservation by providing both technologies and the feeling of self-efficacy, particularly on the part of older people operating non-specialized farms close to the road. In the absence of pro-active government, these results can help bring the voice of rural Myanmar villagers to world attention. ? 2010 Springer Science+Business Media B.V.